VIRTUAL SUBSTATION um sistema de realidade virtual para treinamento de operadores de subestações elétricas - Silva, Reginaldo Costa (2012)
For the electricity be generated and distributed safely, our country has a huge and complex distribution network. Within such a network, an important component of the electrical substations. They are responsible for the control, supervision, protection and metering the flow of this energy. Due to the enormous technological advances of recent years and the great diversity of existing substation projects, the operation of which can only be performed by highly skilled professionals. Such is the demand for qualified by these professionals, their training becomes time consuming, complicated and expensive. Thus, the Virtual Reality technology proves an interesting alternative, since it enables the creation of highly realistic learning objects, with which the aspiring trader can interact without putting your life at risk and without causes financial losses. The purpose of this study is to investigate virtual reality techniques for building training environments suitable for these professionals. To perform validation of these techniques, we built a system called Virtual Reality Virtual Substation in which students can interact with a transformer power through manipulation of 3D objects or panel traditional supervisory system. Both of these views (2D and 3D) are shown simultaneously, so that the user of the system can verify how one interferes with the other. The steps performed by the trainee during the training session are stored in a System Manager database and can be retrieved by their instructor, via a 3D environment itself. After the construction of the prototype, it was presented to students of Electrical Engineering and professionals who validated his contribution as a pedagogical tool.